Innovation team members: emotive outlook and profiles comparisons - Swart, Christina (Research of GSB, 2017)
Continuous innovation provides competitive advantage to organisations. Teams are considered as a vehicle for achieving innovative objectives, provided that they implement projects successfully. Several studies reported requirements on what constitute the most suitable team composition to ensure innovation success. The question remained unanswered as to what could be considered to increase the possibility and probability of innovation implementation team success. It was evident from the literature review that solutions could be provided should such challenges be viewed from a multi-disciplinary perspective. The emphasis and impact of team members' emotions were emphasised as an additional insight into optimising success for implementing innovation projects. The theoretical framework guiding this study was the Emotional Style Theory of Davidson and Begley (2012). This affective neuro scientific theory was approached from an industrial psychologist point of view. This research introduced the concept of emotive outlook depicting six constructs namely: mental acuity, self/reality orientation, emotional fitness/change agility, emotional management(self), social sensitivity and sensitivity to context. The study's main contribution was examining and comparing the emotive outlook profiles and patterns of successful and unsuccessful innovation project implementation teams, within the financial services industry. Data was collected from an International Case (providing data from a multi-national company's operations in nine African countries) and a National Case (providing data from three Namibian Institutions). The total sample size was 169 participants. In this mixed methods convergent parallel design study, the quantitative results of certain assessments and the qualitative findings utilising semi-structured interviews and focus group discussions were merged, at the interpretation stage. The purposes of complementarity, completeness, diversity and compensation were achieved when the results were merged. The major contributions of this study were the findings that successful innovation implementation teams were characterized by intra-psychological strengths and cognitive abilities. The research findings concluded a weak focus on interpersonal aspects and team dynamics. The strengths of teams were found to be a reflection of the individual team members' strengths (mental acuity, emotional self-management, self-awareness and emotional intelligence). This led to postulations regarding team dynamics for innovation implementation teams and the importance of separating these teams from, for example, the creative teams in the innovation process. The context which could contribute to the success of these teams was highlighted by the qualitative strand of this research. The knowledge contribution of this study was the prioritising of the emotive outlook constructs presented as a formula. From a scholarly point of view mixed methods research was presented as an exciting methodological choice addressing business challenges. Practice implications were presented on team as well as Innovation Sponsors/ Champions selection criteria and Generation Y. Importantly, interesting areas for possible future research considerations were opened by this study.